Public attitudes in Japan toward participation in whole genome sequencing studies - Okita, Taketoshi (Hum Genomics, 2018)
BACKGROUND: Recent innovations in gene analysis technology have allowed for rapid and inexpensive sequencing of entire genomes. Thus, both conducting a study using whole genome sequencing (WGS) in a large population and the clinical application of research findings from such studies are currently feasible. However, to promote WGS studies, understanding and voluntary participation by the general public is needed. Therefore, it is essential to investigate the general public’s attitude toward and understanding of WGS studies. The primary goal of our research is to investigate these issues and to discover how they relate to research participation in WGS studies. METHODS: A survey of awareness regarding WGS and studies using WGS was conducted with a sample of 2000 or more participants using a self-administered questionnaire posted on the Internet between February 20 and 21, 2015. Prior to the survey, we briefly explained WGS and WGS study-related issues to the respondents in order to provide them with the minimum knowledge required to answer the questionnaire. We then conducted an analysis, including cross-classification. RESULTS: For the question regarding interest in WGS, 46.6% of participants responded “Yes.” 70.7% of all respondents said that they were interested in some kinds of findings that could be obtained from WGS studies. Regarding participation in WGS studies, 29.0% were interested in participating. The demographic factors significantly related to attitudes toward research participation were age, level of education, and employment status. The results also suggest that concerns about WGS have a positive effect on people’s willingness to participate. Furthermore, it was shown that for people who were not interested in their gene-related information, concerns about WGS negatively impacted their willingness to participate. However, for people who were interested in their gene-related information, their concerns might not have impacted their willingness to participate. DISCUSSION AND CONCLUSIONS: This research has shown several key factors that affect the willingness of the general public for the participation to the WGS studies. One of the unexpected findings is that concerns toward WGS studies generally have positive effect on the peoples’ attitude. It will be interesting to further investigate into the various types of concerns that people in different groups have about WGS.